Analisis Tingkat Pencemar Sulfur Dioksida (SO2) Akibat Aktivitas Kendaraan Bermotor di Kota Kendari: (Studi Kasus: Jalan Christina Marta Tiahahu Kelurahan Lepo-lepo, Kecamatan Baruga) - Alisain, Muhamad; Rosdiana, Rosdiana; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
The air quality on our planet is deteriorating over time due to air pollution. Air pollution causes changes in the composition of the atmosphere, where an excessive concentration of pollutants can damage property, endanger living beings, and disrupt overall air quality. Emissions from fuels generated by motor vehicles pose a danger to the environment and have an adverse impact on human health. This study aims to: (1) Determine the density of traffic vehicles on Christina Martha Tiahahu Street in Kendari City. (2) Determine the level of sulfur dioxide (SO2) air pollution on Christina Martha Tiahahu Street in Kendari City. The results of the analysis of ambient air sample levels were carried out at the Biomolecular and Environmental Laboratory, Faculty of Mathematics and Natural Sciences, Haluoleo University, Kendari. The results showed that the ambient SO2 concentration in the time range of 07.00-08.00 WITA, with a temperature of around 28°C and a humidity of 82Rh, indicated that the measured SO2 content reached 8.45 μg/m3. For the daytime in the time range of 12.00-13.00 WITA with a temperature of 29°C and a humidity of 82Rh, the measured SO2 content reached 22.14 μg/m3. However, for the afternoon during 16.00-17.00 WITA with a temperature of 29°C and a humidity of 82Rh, the results showed an SO2 concentration of 13.4 μg/m3.